2019
DOI: 10.3389/fnins.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Potentiation Alters Perceptual Eye Dominance Plasticity Induced by a Few Hours of Monocular Patching in Adults

Abstract: A few hours of monocular deprivation with a diffuser eye patch temporarily strengthens the contribution of the deprived eye to binocular vision. This shift in favor of the deprived eye is characterized as a form of adult visual plasticity. Studies in animal and human models suggest that neuromodulators can enhance adult brain plasticity in general. Specifically, acetylcholine has been shown to improve certain aspects of visual function and plasticity in adulthood. We investigated whether a single administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 63 publications
(107 reference statements)
2
25
1
Order By: Relevance
“…Interestingly, they found no cumulative effect, which suggested to them that the phenomenon acts in an all-or-none fashion. Separately, to test whether the acetylcholine neuromodulator enhances visual system's plasticity during short-term deprivation, Sheynin etal, 42 administered a single dose of 5mg donepezil (cholinergic inhibitor) before commencing the experiment. They found that the cholinergic dosage acted to reduce the magnitude and duration of the shift in dominance to the previously deprived eye.…”
Section: Short-term Monocular Deprivation Temporarily Boosts Sensory mentioning
confidence: 99%
“…Interestingly, they found no cumulative effect, which suggested to them that the phenomenon acts in an all-or-none fashion. Separately, to test whether the acetylcholine neuromodulator enhances visual system's plasticity during short-term deprivation, Sheynin etal, 42 administered a single dose of 5mg donepezil (cholinergic inhibitor) before commencing the experiment. They found that the cholinergic dosage acted to reduce the magnitude and duration of the shift in dominance to the previously deprived eye.…”
Section: Short-term Monocular Deprivation Temporarily Boosts Sensory mentioning
confidence: 99%
“…Using this paradigm, we computed median phase durations as well as overall fractions for each of our five percept states (i.e., left, right, balanced mixed, mixed left, and mixed right; Figure 2B), allowing us to calculate ratios between the median phase durations of exclusive percepts (exclusive left vs. exclusive right) and mixed percepts (mixed left vs. mixed right). Although mean rivalry phase durations are used commonly in the literature to quantify perceptual dominance during rivalry (Blake & Logothetis, 2002;Klink et al, 2010;Lunghi et al, 2011;Sheynin et al, 2019;Zhou, Gao, White, Merk, & Yao, 2004), calculating the mean of the distribution is prone to be biased in favor of longer phase durations (Zhou et al, 2004); therefore, to account for this, we used the median rather than the mean of the phase duration distribution as a measure of perceptual dominance for each category. Obtaining phase durations of overall mixed visibility We concatenated adjacent mixed percepts reported using the three mixed states in the original task to compute a new aggregated mixed percept state from which we extracted the median duration of mixed visibility.…”
Section: Preprocessing and Statistical Analysismentioning
confidence: 99%
“…MRS measurements made after visual and motor cortex cTBS have indicated increased visual cortex GABA concentration (25,28), an effect that would be expected to reduce mixed percept duration and increase perceptual dominance (29,55). A possible explanation for our observation of reduced mixed percept duration following visual cortex cTBS relates to changes in the signalto-noise ratio within visual cortex neural activity (25,26,56).…”
Section: Increased Mixed Percept Duration Following Visual Cortex Ctbsmentioning
confidence: 75%